Characterization of Coleus blumei viroid 5 (CbVd-5) from Coleus blumei in Malaysia - Zulkifli, Nurnajwa (2017)
Coleus blumei is an ornamental plant in the family Lamiaceae which originated from Indonesia. It produces many tiny beautiful flowers and has colorful of kaleidoscopic leaves with nettle-like edges and bronze-colored leaves which popularly used for landscape. However, it is known to be infected by viroids which is the smallest plant pathogen. Coleus blumei viroid (CbVd) is a member of family Pospiviroid which have been reported to cause serious problem in Coleus blumei species in all over the world. Its infection can be either asymptomatic or result in symptoms including dwarfing, chlorosis or purple pigmentation on leaves margin depending on the cultivar. Coleus blumei is susceptible to infection by six CbVd genotypes (genus, Coleviroid; family, Pospiviroid), CbVd-1 to CbVd-6. In Malaysia, only CbVd-1 has been discovered and the presence of other CbVd viroids has not been reported yet. However, CbVd-5 has been reported in Indonesia and China. The objective of this study are to detect and characterize CbVd-5 in Coleus blumei using reverse transcription polymerase chain reaction (RT-PCR) and two dimensional gel electrophoresis (2D-PAGE) and sequencing. 32 samples of Coleus blumei showing viroid-like infection symptoms and non-symptomatic plants were collected around Selangor, Kedah and Melaka. Total nucleic acid were extracted and the presence of CbVd-5 was detected by RT-PCR using CbVd-5 specific primers. RT-PCR analysis showed that 10 out of 32 Coleus blumei were positive CbVd-5. All RT-PCR positive samples produced an amplicon that ranged 250-300 bp on 1.5% agarose gel. Three out of 10 samples positive with CbVd-5 were samples showing viroid infection-like symptom in which, one from Selangor, and two from Kedah. Meanwhile, seven out of 10 samples positive with CbVd-5 were non-symptomatic samples in which two from Selangor, one form Kedah and four from Melaka. Sequencing of the amplicons from the positive samples showed variants of CbVd-5 with 98-99% similarity to Coleus blumei viroid 5 clone 1, complete genome (Genebank:FJ151370.1). Sequence analysis of clones for Selangor sample did not yield good sequencing result. The circularity of the CbVd RNA by 2D-PAGE was not able to be proven. However, the presence of CbVd-5 in Coleus blumei species in Malaysia was confirmed.